2016
DOI: 10.1007/s13201-016-0494-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable conversion of agro-wastes into useful adsorbents

Abstract: Preparation and characterization of raw and activated carbon derived from three different selected agricultural wastes: kola nut pod raw and activated (KNPR and KNPA), bean husk raw and activated (BHR and BHA) and coconut husk raw and activated (CHR and CHA) were investigated, respectively. Influences of carbonization and acid activation on the activated carbon were investigated using SEM, FTIR, EDX, pH pzc and Boehm titration techniques, respectively. Carbonization was done at 350°C for 2 h followed by activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 45 publications
4
36
0
Order By: Relevance
“…3b, there are formations of several well-developed pores on the CHA (Fig. 2b), owing to the effects of activating agent at high temperature which broke down the lignocellulosic materials followed by volatilization of volatile compound(s) (Bello et al 2012(Bello et al , 2017c. This demonstrated that H 3 PO 4 activation leads to creation of well-developed pores on the precursor surfaces, thereby leading to AC with large porous surface areas and structures.…”
Section: Characterization Of Activated Carbon Preparedmentioning
confidence: 92%
“…3b, there are formations of several well-developed pores on the CHA (Fig. 2b), owing to the effects of activating agent at high temperature which broke down the lignocellulosic materials followed by volatilization of volatile compound(s) (Bello et al 2012(Bello et al , 2017c. This demonstrated that H 3 PO 4 activation leads to creation of well-developed pores on the precursor surfaces, thereby leading to AC with large porous surface areas and structures.…”
Section: Characterization Of Activated Carbon Preparedmentioning
confidence: 92%
“…Four portions of 1.0 g each of raw and GALAC samples were kept in contact with separate solutions of 10-15 ml of 0.1 M NaOH, 0.1 M NaHCO 3 and 0.05 M Na 2 CO 3 for determining acidic groups and 0.1 M HCl for the basic groups composites respectively at temperature of 48 h. Afterwards, the resulting aqueous solutions were back-titrated with 0.1 M HCl for acidic and 0.1 M NaOH for basic groups. The types and numbers of acidic sites were calculated using previous procedure [45,53]. Briefly, for the determination of the numbers and types of acidic sites, certain considerations were made that NaOH neutralizes carboxylic, lactonic and phenolic groups, Na 2 CO 3 neutralizes carboxylic and lactonic groups and that NaHCO 3 neutralizes only carboxylic groups.…”
Section: Determination Of Oxygen-containing Functional Groupsmentioning
confidence: 99%
“…Recently, many researchers have looked into modifying the surface of adsorbents for total or complete removal of various dyes from the aqueous solution and generally reported that modifying agents increase the adsorption site(s) for both cationic and anionic dyes. Examples includes: guava leaf [39] bamboo [40,41], plant leaf [42], coconut leaves [43,44], kola nut and bean husk [45,46], ficus racemosa [47,48], Prunus Dulcis [49], durian Leaf [50], dead Leaves of plane trees [51], prunus dulcis [49], Moringa oleifera leaf [52,53], C. camphora leaves [54], berry leaves [55], Glossogyne tenuifolia leaves [56]. Several authors have demonstrated the peculiarity of agricultural-based materials to remove various dyes having diverse molecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…The significant increase of acidic groups when compared to the basic group, suggests that the majority of functional group on the adsorbent surface are acidic. Prominent acidic group indicate more oxygenated functional groups, resulting in higher adsorption of dyes [50,51].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The pH PZC was found to be 3.05 for MOSPAC. Cation adsorption is enhanced at pH value higher than pH PZC , while adsorption of anions is favoured at pH value less than pH PZC [41,[50][51][52].…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 99%